2018
DOI: 10.1248/bpb.b18-00015
|View full text |Cite
|
Sign up to set email alerts
|

An E3 Ubiquitin Ligase, Synoviolin, Is Involved in the Degradation of Homocysteine-Inducible Endoplasmic Reticulum Protein

Abstract: Homocysteine-inducible endoplasmic reticulum (ER) protein (Herp) is an ER stress-inducible membrane protein involved in ER-associated degradation. Herp expression is maintained at low levels through a strict regulatory mechanism, but the details of this mechanism and the reasons why Herp expression is restricted in this manner remain unclear. Here, we show that Herp degradation involves synoviolin, an ER-resident E3 ubiquitin ligase. Herp protein levels were found to be markedly elevated in synoviolin-null cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…On the other hand, while the ERAD complex component HERP protein was degraded by the UPS ( Hori et al, 2004 ), EDEM1 and ERManI proteins were eliminated by the autophagy machinery ( Le Fourn et al, 2013 ; Park et al, 2014 ; Benyair et al, 2015 ). An ER-localized E3 ligase synoviolin protein was shown to ubiquitylate HERP protein and control its degradation by proteasome ( Maeda et al, 2018 ). Yet, other ERAD-related components, EDEM1 and Derlin2 as well as ubiquitylated EDEM1 proteins colocalized with cytoplasmic aggregates and autophagy receptors p62 and NBR1, they were degraded by selective autophagy ( Le Fourn et al, 2013 ; Park et al, 2014 ).…”
Section: The Ups-autophagy Connectionmentioning
confidence: 99%
“…On the other hand, while the ERAD complex component HERP protein was degraded by the UPS ( Hori et al, 2004 ), EDEM1 and ERManI proteins were eliminated by the autophagy machinery ( Le Fourn et al, 2013 ; Park et al, 2014 ; Benyair et al, 2015 ). An ER-localized E3 ligase synoviolin protein was shown to ubiquitylate HERP protein and control its degradation by proteasome ( Maeda et al, 2018 ). Yet, other ERAD-related components, EDEM1 and Derlin2 as well as ubiquitylated EDEM1 proteins colocalized with cytoplasmic aggregates and autophagy receptors p62 and NBR1, they were degraded by selective autophagy ( Le Fourn et al, 2013 ; Park et al, 2014 ).…”
Section: The Ups-autophagy Connectionmentioning
confidence: 99%
“…Among the differentially expressed proteins, SYVN1, an E3 ligase was found to be upregulated threefold in the treated cells (Figure 3A). Based on our previous studies demonstrating the ubiquitin-proteasomal degradation of MNK1/2 induced by VNLG-152R in breast (9,18) and prostate (33, 34) cancer cell lines and the role of SYVN1 as an E3 ligase involved in ubiquitination and proteasomal degradation of several proteins (35)(36)(37)(38)(39)(40)(41)(42), we hypothesized that SYVN1 might play a key role in the ubiquitination and subsequent degradation of MNK1/2. Immunoblotting for SYVN1 confirmed its increased expression in VNLG-152R-treated cells compared to the control with concomitant decrease in MNK1/2 and its product p-eIF4E (Figure 3B).…”
Section: Syvn1 Is Constitutively Upregulated In Vnlg-152r-treated Tnb...mentioning
confidence: 99%
“…For example, it was shown that one of the main agents contributing to the accumulation of Aβ and tau proteins is homocysteine (Shirafuji et al , 2018). Homocysteine triggers the endoplasmic reticulum protein HERP, stimulating the c-secretase activity and increasing Aβ accumulation in the brain (Maeda et al , 2018). In hyperlipidemia, diabetes, hypertension, etc., the brain exposes to ischemic and hypoxic conditions (Cheng et al , 2018), which impairs the blood and cerebrospinal fluid flow and decreases aggregated proteins clearance.…”
Section: Dementia Risk Factorsmentioning
confidence: 99%